Implementación de una unidad de artritis reumatoide temprana en pacientes chilenos derivados desde centros de atención primaria de salud - Espinoza, Francisco; Monckeberg, Gustavo; Hassi, Isabel; Queirolo, Alejandra; Chicao, Fernando; Sandoval, Ximena; Jorquera, Evelyn; Badilla, Alejandro (Revista Médica de Chile, 2018)
Background: Early recognition of rheumatoid arthritis (RA) provides clinical benefits in terms of remission induction, reduced disease progression, and eventually treatment free remission. Aim: To describe the setting of a Unit devoted exclusively to the recognition and treatment of early RA in patients referred from primary healthcare centers (PHC) in Chile. Materials and Methods: Patients were referred from nine participating PHC from 2014 through 2016. PHC physicians received a formal training to enhance criteria recognition and program adherence. Mandatory referral criteria were an age above 17 years, and arthralgia of less than 1-year duration, plus at least one of the following: morning stiffness of more than 30 minutes, swelling involving more than 3 joints for more than 1 month, a positive squeeze test or abnormal inflammatory serum markers. Results: One hundred twenty patients aged 45 ± 12 years (90% women) were assessed at the early rheumatoid arthritis unit. Median time to referral from PHC to the Unit was 14.6 days. The median duration of symptoms for the overall sample of patients was 10.8 months. RA was identified in 43 patients (36%), with a delay between onset of symptoms and diagnosis of 8.3 months. Regarding the performance of referral criteria, the most sensitive was morning stiffness (80%,sensitivity 95% confidence intervals (CI) 64- 89%) and synovitis was the most specific (specificity 83%, 95% CI 72-90%). The positive predictive value of the three clinical criteria altogether was 68.1% (95%CI 47- 83%). Conclusions: Institution of an early RA unit was feasible within the Chilean healthcare system enabling the identification of early RA in one-third of patients.